Folkloric Speech and Education - Loayza Maturrano, Edward Faustino (2010)
The present paper approaches the existent relationship between education and the folkloric speech, analyzing its current problem in the pedagogic practice, its justified importance in the human formation, and the paper that completes the 'course' of 'Language and Castilian Literature' -now call "area" and "Communication" respectively- in the process of teaching-learning of the basic fonnal education and superior. Also, an educational proposal is sketched from the course of language and Literature to promote and to develop in the formal education the conscience sociolinguistic on the folklore verbal multicultural characteristic of our country.